2019
DOI: 10.1371/journal.pone.0213445
|View full text |Cite
|
Sign up to set email alerts
|

Combining quick sequential organ failure assessment score with heart rate variability may improve predictive ability for mortality in septic patients at the emergency department

Abstract: BackgroundAlthough the quick Sequential Organ Failure Assessment (qSOFA) score was recently introduced to identify patients with suspected infection/sepsis, it has limitations as a predictive tool for adverse outcomes. We hypothesized that combining qSOFA score with heart rate variability (HRV) variables improves predictive ability for mortality in septic patients at the emergency department (ED).MethodsThis was a retrospective study using the electronic medical record of a tertiary care hospital in Singapore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
1
14
0
9
Order By: Relevance
“…In the literature AUROCs were found for SOFA and qSOFA for in-hospital mortality in a large validation dataset: AUC = 0.74 (all) and 0.79 (non-ICU) for SOFA and 0.66 (all) and 0.81 (non-ICU) for qSOFA [ 27 ]. Similar results are observed for recent studies outside the ICU with AUROC ranging from 0.77–0.83 for SOFA [ 28 32 ] and 0.63–0.77 for qSOFA [ 29 , 30 , 33 35 ]. MEDS is also a predictor of mortality.It had an AUC of 0.82 and 0.76 for its derivation and validation cohorts, respectively [ 11 ], although significant variability has been seen in the literature with AUC ranging from 0.67–0.77 in five recent studies [ 36 – 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the literature AUROCs were found for SOFA and qSOFA for in-hospital mortality in a large validation dataset: AUC = 0.74 (all) and 0.79 (non-ICU) for SOFA and 0.66 (all) and 0.81 (non-ICU) for qSOFA [ 27 ]. Similar results are observed for recent studies outside the ICU with AUROC ranging from 0.77–0.83 for SOFA [ 28 32 ] and 0.63–0.77 for qSOFA [ 29 , 30 , 33 35 ]. MEDS is also a predictor of mortality.It had an AUC of 0.82 and 0.76 for its derivation and validation cohorts, respectively [ 11 ], although significant variability has been seen in the literature with AUC ranging from 0.67–0.77 in five recent studies [ 36 – 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…A study that employed time-series monitoring at the intensive care unit found that a rise in heart rate was a predictor of sepsis four hours before clinical detection, and that the sensitivity of the heart rate model was 85% combined with other clinical factors [9]. Additionally, a previous study found heart rate variability (HRV) to be an indicator for mortality in sepsis patients [10], being significantly higher in patients who died than in those who survived (31.8 s vs. 23.7 s; p -value = 0.02). In this study, for each 10-beat increase in pulse rate, the risk of inappropriate antibiotic administration went up by 19% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a quick and non-invasive method of evaluating the autonomic modulation of the cardiovascular system, which has been shown to be dysregulated in sepsis [18]. Abnormalities in HRV parameters present themselves far before clinical signs become apparent [19,20] and have been found to correlate well with subsequent patient deterioration and mortality [13,21,22,23,24,25,26]. HRV analysis may thus represent a potentially useful method for the early risk-stratification of septic patients presenting at the ED and can be considered as a standalone predictor or as an augmentation of the other disease severity scores.…”
Section: Introductionmentioning
confidence: 99%